Combining ability analysis for grain yield and quality characters in rice (Oryza sativa) - ROY, S K; SENAPATI, B K (The Indian Journal of Agricultural Sciences, 2012)
Genetic variances were estimated for grain yield and quality characters in rice (Oryza sativa L.) by full-sib and half- sib analysis in 20 F1 hybrids produced from crosses between five high yielding genotypes namely IR 50, IR 62, IET 5656, IET 8002 and IET 6441 as lines and four quality rice genotypes namely Basmati 385, Dudheswar, Kalonunia and Sambamahsuri as testers. The lines were significantly varying for the characters, whereas variances due to testers were significant for all the characters except panicle weight. Line × tester interaction was highly significant for all the characters. Combining ability analysis revealed predominance of non-additive gene action for days to flowering, total tillers/plant, productive tillers/plant, 1000 grain weight, grain yield/plant and kernel elongation ratio; additive gene action for plant height, panicle length, panicle weight, spikelet/panicle, filled grains/panicle, spikelet fertility, grain length, grain breadth, grain length/breadth ratio, grain weight/panicle, kernel length, kernel breadth and kernel length/breadth ratio and both additive and non-additive gene actions for cooked kernel breadth. Among the lines IET 5656 was found to be the best general combiner for grain yield as well as its components and quality characters, while IET 8002 and IET 6441 were superior general combiners for quality characters only. Among the testers Kalonunia was the best general combiner for yield and its components followed by Basmati 385, whereas, for the quality characters Dudheswar was the best general combiner, followed by Basmati 385. The three crosses namely IET 5656 × Kalonunia, IR 50 × Basmati 385 and IR 62 × Sambamahsuri were superior over their superior grain quality parents like Kalonunia, Dudheswar and Sambamahsuri for most of the yield and quality characters. When all the 23 yield and quality characters were considered together in an overall ranking on the basis of specific combining ability for grain yield per plant and kernel elongation ratio as the base characters and the actual field performance of their attributing characters, the cross IET 8002 × Dudheswar was the best performer, closely followed by IR 50 × Basmati 385 and IET 6441 × Dudheswar in this regard.